Potential impingement factors of reading habits at rural library in Malaysia - Mazuki, Raidah; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Asian Network for Scientific Information, 2014)
Rural library in Malaysia is purposively built to combat illiteracy and enhance knowledge possesion among the rural community which is important in order for them to cope with the demand of globalization. The source of the library information is expected to change the lifestyle of the local community. This conceptual study suggests the potential impingement factors for reading habits at the rural library in Malaysia. Based on the document analyses performed, various potential factors that impinge the reading habits at the rural library are identified namely place and the building, adequacy of tools and the librarian. A number of discussion have been placed and it is a hope, such discussion can assist to further cultivate reading habits among the community particularly among those who settle in the rural areas.